2007
DOI: 10.1243/09576509jpe296
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of a contra-rotating tidal current turbine

Abstract: A contra-rotating marine current turbine has a number of attractive features: near-zero reactive torque on the support structure, near-zero swirl in the wake, and high relative interrotor rotational speeds. Modified blade element modelling theory has been used to design and predict the characteristics of such a turbine, and a model turbine and test rig have been constructed. Tests in a towing tank demonstrated the feasibility of the concept. Power coefficients were very high for such a small model and in excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Turbine design is more fully described in [14][15]. In summary, an extension of conventional blade element momentum (BEM) theory was used to predict the geometry of the downstream rotor relative to the specified upstream rotor.…”
Section: Rotor Hydrodynamic Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbine design is more fully described in [14][15]. In summary, an extension of conventional blade element momentum (BEM) theory was used to predict the geometry of the downstream rotor relative to the specified upstream rotor.…”
Section: Rotor Hydrodynamic Designmentioning
confidence: 99%
“…Performance predictions for the turbine are given in [15]; as in the original small model, provision is made for adjusting the blade pitch.…”
Section: Turbine Design At 1/10 Th Scalementioning
confidence: 99%
“…After successful proof of concept trials on a 0.9 m diameter contra-rotating turbine in a towing tank [1], a larger 2.5 m diameter prototype was constructed (see Figure 1). Sea trials in the Clyde estuary confirmed the inherent stability of the contra-rotating design and for the first time provided high-resolution measurements of blade bending moments, from strain gauges attached to blade roots on both rotors.…”
Section: Experimental Turbinesmentioning
confidence: 99%
“…The 2 nd generation contra-rotating marine current turbine developed by the Energy Systems Research Unit (ESRU) at the University of Strathclyde has been widely reported and is now reasonably wellknown [1,2]. Two key features of the design, which uses two rotors with a dissimilar number of blades in close proximity, is: the increased relative shaft speeds enable the elimation of a gearbox in favour of a direct drive permanent magnet, contra rotating generator; and the ability to mitigate/ minimise the reactive torque transmitted to the supporting structure, permitting the use of relatively simple, economic mooring systems and allowing deployments in very deep water.…”
Section: Introductionmentioning
confidence: 99%
“…More efficient MHK turbine designs help to reduce the cost of marine energy and make it more competitive with other forms of energy production. Recent studies of MHK devices [1][2][3][4] mainly focus on quasi-unsteady modeling techniques. Accurately modeling the unsteady effect of the rotor fluid dynamics is still a challenge.…”
Section: Introductionmentioning
confidence: 99%